Given: F(x) = 2x and G(x) = x 2 + 2
Find (G - F)(x).

Question|Asked by ardonav23

Asked 3/11/2016 9:19:55 AM

Updated 364 days ago|4/25/2023 12:33:48 AM

1 Answer/Comment

s

Question|Asked by ardonav23

Asked 3/11/2016 9:19:55 AM

Updated 364 days ago|4/25/2023 12:33:48 AM

1 Answer/Comment

Rating

3

The x-values are equally spaced, while the y-values decline to a minimum of 2 before increasing again. The first differences are -1, 1, 3, 5, and the second differences are always 2. This means that the rule can be written using a polynomial of the second degree.

Because the minimum of f(x) occurs at x = 0, there is no horizontal shift of the quadratic function's vertex. f(1) - f * (0) = 1, hence the quadratic's vertical scale factor is 1.

The quadratic with the vertex (0, 2) and the vertical scale factor of one is...

f(x) = 1 * (x - O) ^ 2 + 2

f(x) simplified = x 2 + 2

Because the minimum of f(x) occurs at x = 0, there is no horizontal shift of the quadratic function's vertex. f(1) - f * (0) = 1, hence the quadratic's vertical scale factor is 1.

The quadratic with the vertex (0, 2) and the vertical scale factor of one is...

f(x) = 1 * (x - O) ^ 2 + 2

f(x) simplified = x 2 + 2

Added 364 days ago|4/25/2023 12:33:48 AM

This answer has been confirmed as correct and helpful.

Solve each equation.
0.2x2 + 1.2 = 3.4
**Weegy:** The method I would choose to solve this equation 2x2 ? 7 = 9 is Quadratic Equations. **User:** Solve each equation.
0.2x2 + 1.2 = 3.4
**Weegy:** The method I would choose to solve this equation 2x2 ? 7 = 9 is Quadratic Equations. **User:** Solve each equation. Leave the answer as an improper fraction.
16x2 = 49 **User:** 0.2x2 + 1.2 = 3.4 **Weegy:** x= -4,1 **User:** 3x2 + 2 = 11 - x2 (More)

Question|Asked by ardonav23

Not Answered

Updated 364 days ago|4/25/2023 12:34:22 AM

2 Answers/Comments

3x^2 + 2 = 11 - x^2

3x^2 + x^2 = 11 - 2

4x^2 = 9

x^2 = 9/4

x = 3/2 or x = -3/2

3x^2 + x^2 = 11 - 2

4x^2 = 9

x^2 = 9/4

x = 3/2 or x = -3/2

Added 3/4/2016 5:17:25 PM

0.2x^2 + 1.2 = 3.4

0.2x^2 = 3.4 - 1.2 = 2.2

x^2 = 2.2/0.2 = 11

x = ± sqrt 11

0.2x^2 = 3.4 - 1.2 = 2.2

x^2 = 2.2/0.2 = 11

x = ± sqrt 11

Added 364 days ago|4/25/2023 12:34:22 AM

This answer has been confirmed as correct and helpful.

Choose the constant term that completes the perfect square trinomial.
x 2 - 18x User: Choose the constant term that completes the perfect square trinomial.
y2 + 0.1y

Question|Asked by ardonav23

Not Answered

Updated 2/5/2023 1:08:19 AM

1 Answer/Comment

The constant term that completes the perfect square trinomial. y^2 + 0.1y is 0.01/4=0.0025.

Rewrite as: y^2 + 0.1y + 0.0025.

Rewrite as: y^2 + 0.1y + 0.0025.

Added 2/5/2023 1:08:19 AM

This answer has been confirmed as correct and helpful.

Which of the following statements describes one part of completing the square for x 2 + 4x = 32? **Weegy:** 2(4x + 2) = 8x + 4 **User:** Which of the following statements describes one part of completing the square for x 2 + 4x = 32?
Take the square root of 36 and add 2.
Take the square root of 32 and subtract 2.
Take the square root of 36 and subtract 2. **Weegy:** 2(4x + 2) = 8x + 4 **User:** Choose the constant term that completes the perfect square trinomial.
y 2 + 5y
**Weegy:** y^2 + 5y + (25/4) is a perfect square trinomial.
y^2 + 5y + (25/4) = [y + (5/2)]^2 **User:** Choose the constant term that completes the perfect square trinomial.
y2 + 0.1y (More)

Question|Asked by ardonav23

Updated 2/5/2023 12:51:38 AM

2 Answers/Comments

The constant term that completes the perfect square trinomial. y^2 + 0.1y is 0.01/4=0.0025.

Rewrite as: y^2 + 0.1y + 0.0025.

Rewrite as: y^2 + 0.1y + 0.0025.

Added 2/5/2023 12:48:55 AM

This answer has been confirmed as correct and helpful.

The constant term that completes the perfect square trinomial. y^2 + 5y is: 5/4 = 1.25.

Rewrite as: y^2 + 5y + 1.25.

Rewrite as: y^2 + 5y + 1.25.

Added 2/5/2023 12:51:38 AM

This answer has been confirmed as correct and helpful.

The following statements describes one part of completing the square for x 2 + 4x = 32 is: Take the square root of 36 and subtract 2.

Added 2/5/2023 12:55:26 AM

This answer has been confirmed as correct and helpful.

Which of the following equations is an equation formed when completing the square on y 2 - 12y = -27?

Question|Asked by ardonav23

Updated 2/5/2023 12:47:17 AM

1 Answer/Comment

The following equations is an equation formed when completing the square on y^2 - 12y = -27 is: y^2 - 12y + 27 = 0.

Added 2/5/2023 12:47:17 AM

This answer has been confirmed as correct and helpful.

39,074,178

questions answered

There are no comments.